2021
DOI: 10.1038/s41419-021-03842-1
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 regulates primordial follicle activation through mTOR signaling pathway

Abstract: Primordial follicle pool established perinatally is a non-renewable resource which determines the female fecundity in mammals. While the majority of primordial follicles in the primordial follicle pool maintain dormant state, only a few of them are activated into growing follicles in adults in each cycle. Excessive activation of the primordial follicles accelerates follicle pool consumption and leads to premature ovarian failure. Although previous studies including ours have emphasized the importance of keepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…This energy shortage activates AMPK to increase catabolism, especially glycolysis [ 20 ], and enhanced glycolysis triggers the inhibition of AMPK and the subsequent activation of mTOR in the mouse brain [ 30 ]. In this study, the standard medium for culturing ovarian tissues contains pyruvate [ 10 12 ]. Short-term pyruvate deprivation promotes glycolysis via negative feedback of AMPK, and then enhanced glycolysis subsequently activates mTOR signaling by decreasing AMPK activity in mouse ovaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This energy shortage activates AMPK to increase catabolism, especially glycolysis [ 20 ], and enhanced glycolysis triggers the inhibition of AMPK and the subsequent activation of mTOR in the mouse brain [ 30 ]. In this study, the standard medium for culturing ovarian tissues contains pyruvate [ 10 12 ]. Short-term pyruvate deprivation promotes glycolysis via negative feedback of AMPK, and then enhanced glycolysis subsequently activates mTOR signaling by decreasing AMPK activity in mouse ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of oocyte growth is lifted, and the follicle begins to grow. Other molecules have also been reported to be involved in the activation of primordial follicles by regulating the above signaling pathways, including mitogen-activated protein kinase (MAPK3/1), E-cadherin, and histone deacetylase 6 (HDAC6) [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the formation of the final primordial follicles pool, the periodic activation of primordial follicles will continuously deplete the number of primordial follicles, shortening the reproductive lifespan. Therefore, adequately regulating the speed of primordial follicle activation will prolong the reproductive life of the ovaries (5). A number of studies have previously reported that KN93 is a specific inhibitor of CaMKII that can regulate various physiological and pathological processes by specifically inhibiting CaMKII activity (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…According to the previously reported morphological and functional changes that occur during follicular development, follicles can be divided into primordial, primary, secondary and mature follicles (2)(3)(4). In particular, formation and activation of primordial follicles is key for determining reproductive ability (5). In the majority of mammalian species, the formation of primordial follicles typically occurs during the embryonic stages or around birth (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, primordial follicle activation by mTOR signalling was associated with decreased HDAC6 activity. This finding may be of importance for the management of premature ovarian failure (POF) as an alternative approach to primordial follicle in vitro activation (IVA) [ 48 ]. HDAC8 has a similarly indispensable role as HDAC6 and is located on spindle poles.…”
Section: Epigenetics Of Germ Cells Developmentmentioning
confidence: 99%